Engajamento cívico e escolaridade superior: as eleições de 2014 e o comportamento político dos brasileiros - Dias, André Luiz Vieira; Kerbauy, Maria Teresa Miceli (Universidade Federal do Paraná, 2015)
Abstract The objective of this article is to analyze the influence of the variable schooling on the political behavior of Brazilians. It starts from the assumption that this is an independent variable capable of awakening a more interested, participatory and coherent behavior, therefore, engaged citizens. In this sense, we seek to verify that Brazilian citizens are informed and interested in politics; motivated to participate in elections and other political activities; and their assessment and satisfaction with the democratic process. In particular, there is the behavior of those who have completed higher education, compared to other levels of education in order to identify distinct behavioral patterns. From the data obtained by ESEB 2014 and descriptive analysis of the data, we applied the logistic regression model relating the variable schooling than other variables grouped into four categories: a) socio-economic aspects; b) information and interest in politics; c) participation in the elections, in traditional political activities and other political activities; and d) evaluation and political satisfaction. Thus, it turns out that Brazilians are little or not at all interested in politics; participate in the elections but not in the traditional activities and new forms of political engagement; They support and are fairly satisfied with democracy. For the most educated, we have a predominance of women, a younger audience and with family income subtly than the less educated. Those who have completed higher education tend to behave differently: they are slightly more informed and interested in politics; despite the low percentages found, they are the ones that participate in political activities in general; They are the ones who support democracy, but the most dissatisfied with their operation. This study allows us to understand the behavior patterns of Brazilians and, more specifically, the most educated, poorly studied by political science in Brazil.

Resumo O artigo tem como objetivo analisar a influência da escolaridade sobre o comportamento político dos brasileiros. Supõe-se que a escolaridade é capaz de despertar um comportamento mais interessado, participativo e coerente, portanto, engajado, dos cidadãos. Nesse sentido, busca-se verificar (i) se os cidadãos brasileiros são informados e interessados por política; (ii) motivados em participar das eleições e outras atividades políticas e (iii) sua avaliação e satisfação em relação ao processo democrático. Destaca-se o comportamento daqueles que possuem o ensino superior completo, em comparação aos demais níveis de escolaridade, no intuito de identificar padrões comportamentais distintos. A partir dos dados obtidos pelo ESEB 2014, além da análise descritiva dos dados, aplicou-se o modelo de regressão logística, relacionando a variável escolaridade superior a outras variáveis agrupadas em quatro categorias: (a) aspectos socioeconômicos; (b) informação e interesse por política; (c) participação nas eleições, em atividades políticas tradicionais e em outras atividades políticas; (d) avaliação e satisfação política. Dessa maneira, verifica-se (i) que os brasileiros são pouco ou nada interessados por política; (ii) participam das eleições mas não das atividades tradicionais e novas formas de engajamento político; (iii) apoiam e estão razoavelmente satisfeitos com a democracia. Em relação aos mais escolarizados, temos o predomínio de mulheres, um público mais jovem e com renda familiar sutilmente superior à dos menos escolarizados. Aqueles que possuem o ensino superior completo tendem a se comportar de forma distinta: são levemente mais informados e interessados por política; apesar dos baixos percentuais encontrados, são os que mais participam das atividades políticas em geral; são os que mais apoiam a democracia, porém os mais insatisfeitos com o seu funcionamento. Esse estudo nos permite compreender os padrões comportamentais dos brasileiros e, mais especificamente, dos mais escolarizados, ainda pouco estudados pela Ciência Política no Brasil.
Keywords: political behavior; civic engagement; higher education; political interest; political participation; comportamento político; engajamento cívico; escolaridade superior; interesse político; participação política